Trinidad and Tobago : 2006 Article IV Consultation; Staff Report; Staff Statement; and Public Information Notice on the Executive Board Discussion. (IMF Staff Country Reports; Country Report ;, 2007)
This 2006 Article IV Consultation highlights that economic developments in Trinidad and Tobago continue to be underpinned by a favorable international environment. Surging energy prices, the exploitation of new gas fields, and an expansion of industrial capacity helped sustain robust economic activity. However, there are signs that the economy is operating at, or near, potential. The monetization of foreign currency energy receipts by the government has introduced a substantial degree of liquidity into the financial system. The banking sector remains profitable, nonperforming loans are low, and provisioning increased compared with the last year.